(Ny)materielle fusioner. Om krops- og kærlighedsfremstillinger hos Amalie Smith, Bjørn Rasmussen og Josefine Klougart - Krarup, Eva Magelund (Passage - Tidsskrift for litteratur og kritik, 2017)
Eva Magelund Krarup: “(New)Material Fusions. On the Representation of Bodies and the Conception of Love in Works by Amalie Smith, Josefine Klougart and Bjørn Rasmussen” The article examines how the representation of the characters in three contemporary Danish literary works can be understood and analysed through new materialist theory, especially through Jane Bennett’s concept of vibrant matter and her theory of assemblages. I examine how, and to what extent, the characters can be conceived of as open systems of (vibrant) materiality, and furthermore which role love plays in this representation of the characters’ feelings of connectedness to others and the world.